Maple syrup urine disease in Brazil: a panorama of the last two decades - Silvani Herber; Ida Vanessa D. Schwartz; Tatiéle Nalin; Cristina Brinkmann Oliveira Netto; José Simon Camelo Junior; Mara Lúcia Santos; Erlane Marques Ribeiro; Lavinia Schüler‐Faccini; Carolina Fischinger Moura de Souza (Jornal de Pediatria (Versão em Português), 2015)
Objective: To characterize a sample of Brazilian patients with maple syrup urine disease (MSUD) diagnosed between 1992 and 2011. Methods: In this retrospective study, patients were identified through a national reference laboratory for the diagnosis of MSUD and through contact with other medical genetics services across Brazil. Data were collected by means of a chart review. Results: Eighty‐three patients from 75 families were enrolled in the study (median age, 3 years; interquartile range [IQR], 0.57‐7). Median age at onset of symptoms was 10 days (IQR 5‐30), whereas median age at diagnosis was 60 days (IQR 29‐240, p = 0.001). Only three (3.6%) patients were diagnosed before the onset of clinical manifestations. A comparison between patients with (n = 12) and without (n = 71) an early diagnosis shows that early diagnosis is associated with the presence of positive family history and decreased prevalence of clinical manifestations at the time of diagnosis, but not with a better outcome. Overall, 98.8% of patients have some psychomotor or neurodevelopmental delay. Conclusion: In Brazil, patients with MSUD are usually diagnosed late and exhibit neurological involvement and poor survival even with early diagnosis. We suggest that specific public policies for diagnosis and treatment of MSUD should be developed and implemented in the country.